Chromogenic in situ Hybridization is a Reliable Alternative to Fluorescence in situ Hybridization for Diagnostic Testing of 1p and 19q Loss in Paraffin‐Embedded Gliomas. (29th November 2012) - Lass, Ulrike; Hartmann, Christian; Capper, David; Herold‐Mende, Christel; von Deimling, Andreas; Meiboom, Maren; Mueller, Wolf
Abstract Recent studies imply the importance of rapid and reliable diagnostic assessment of 1p/19q status in oligodendroglial tumors. To date, fluorescence in situ hybridization (FISH) is the most commonly applied technique. FISH, however, has several technical shortcomings that are suboptimal for diagnostic applications: results must be viewed in a fluorescence microscope, results are usually evaluated by a single investigator only, and signal fading excludes physical archiving. Also, in gliomas, the distinction of diffusely infiltrating tumor cells from reactively altered normal tissue may be challenging in fluorescence microscopy. Dual‐color chromogenic in situ hybridization (CISH) has started to replace FISH in some diagnostic tests performed in pathology. Here, we present the first single institute experience with a side‐by‐side analysis of 1p/19q FISH and CISH in a series of 42 consecutive gliomas. FISH and CISH produced identical results for 1p and 19q in 93% of cases (n = 39/42). Discrepant results were reevaluated by repeated FISH and a polymerase chain reaction (PCR)‐based microsatellite marker analysis for loss of heterozygosity. Reevaluation confirmed CISH data in all three cases. We conclude that CISH is a reliable alternative in 1p/19q testing in paraffin‐embedded tissues likely to be more sensitive to detect 1p/19q status than FISH analysis.